Reducing the engineering skills shortage in the generation sector - Wolfs, Peter; Hargraves, D.; Saha, T. (Curtin University, 2007)
Power generators operate in a competitive market for skilled staff. In 2005 the Queensland generators recognised technical skill development as a critical business risk. Three universities, Central Queensland University, Queensland University of Technology and University of Queensland, have started a five year collaboration with industry to develop to deliver a world-class course work Master of Engineering curriculum in Power Generation. The universities have actively leveraged the synergies between the generators, Stanwell Corporation, CS Energy and Tarong Enegry and industry experts. The program focus is to accelerate the technical competency of power generation engineers. This paper outlines the development of the new program and discusses the operational arrangements between the University and Industry partners.